Aplikasi Media Pembelajaran Ubiquitous Learning Of Angle Dengan Penerapan Pendekatan Otentik - Putra, Muhammad Trio Maulana (Universitas Trunojoyo Madura, 2023)
Covid-19 has given a new personality to education in Indonesia. The use of technology which used to be very limited, but now become an important requirement in the teaching and learning process. The learning process that used to only use blackboards or teaching aids has many limitations and can be completed by utilizing technology with media according to the subject area. Therefore, this research develops a learning media with the name